Kontribusi Faktor Determinan Lingkungan terhadap Prevalensi Kasus Malaria di Kota Sabang, Provinsi Aceh - Teuku Mualana; Said Devi Elvin; Sofyan Sufri (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
The city of Sabang has become a model for Indonesia in malaria elimination. However, currently, there is an increase in malaria cases again in Sabang City and the emergence of a new parasite species, namely Plasmodium knowlesi was transmitted through Macaca fascicularis. This study aims to analyze the influence of environmental, physical, chemical, and biological factors on the prevalence of malaria in Sabang City. This type of research is an observational survey with a cross-sectional design with a sampling technique using cluster-random sampling with a total sample of 100 houses in four research villages. Data was collected using interviews, inspections, and environmental observations carried out on 100 selected houses. Data was analyzed using statistics, univariate in the form of percentage distribution, Chi-square bivariate, and multivariate using logistic regression with the Stepwise method. Surveys of adult mosquitoes were caught at night, from 19.00 to 07.00 once in three houses in 4 villages in the research location. The results of this study showed that the physical environment (p=0.0001), the biological environment (p=0.021), and the chemical environment (p=0.011) were significantly associated with malaria cases. The physical environment was the most influential predictor of malaria cases (OR: 11.096).